COMPARATIVE STUDY OF I-GEL AND LARYNGEAL MASK AIRWAY FOR MINOR SURGICAL PROCEDURES UNDER TOTAL INTRAVENOUS ANAESTHESIA (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Supraglottic airway devices are widely used during short elective procedures because they are easier to insert and less invasive than endotracheal tubes. Among them, the classic laryngeal mask airway (LMA) and the second-generation I-gel are both well-established devices. The present study compared their performance in adults undergoing minor surgical procedures under total intravenous anaesthesia (TIVA). Methods: This hospital-based comparative study was conducted in the Department of Anaesthesiology, Gandhi Medical College and Hospital, Secunderabad, from June 2023 to November 2024. Ninety adult patients aged 18 to 60 years, belonging to ASA I or II, and scheduled for minor elective procedures under TIVA were enrolled and randomly allocated into two equal groups: I-gel (n=45) and LMA (n=45). Outcomes included insertion time, number of attempts, oxygen saturation, haemodynamic variables, airway manipulation, trauma, and postoperative sore throat. Continuous variables were compared using the independent t-test, while categorical variables were analysed using the chi-square test or Fisher’s exact test where appropriate. A p value